Tinjauan Kasus Tentang Dilusi Merek Di Indonesia Dan Thailand - Rika Ratna Permata; tasya safiranita safiranita; Biondy Utama (Jurnal Hukum IUS QUIA IUSTUM, 2019)
Theuse  of  well-known  brands  without  any  license,  in  practice,  often  intentionally  or  unintentionally occurs that not only leads violations but also confusion for the public. The use of a brand without any license -but  not  creating  any  public  confusion -is referred  to  as  brand  dilution.  This  article  aims  to examine the brand dilution case occurred in Indonesia and Thailand by concerning with two issues: first, to  study  the  case  of  IKEA  vs.  IKEMA  occurred  in  Indonesia  and  the  case  of  STARBUCKS  vs. STARBUNG inThailand including in the brand dilution. Second, to study the protection of well-known brands from brand dilution in Indonesia and Thailand. The research used was normative juridical method by means of the statute approach, case approach, analytical approach and comparative approach. The results of this study indicated that first the case of IKEA vs. IKEMA occurred in Indonesia and the case of STARBUCKS vs. STARBUNG is categorized as the brand dilution in consideration to the brand use that has a similarity to well-known brands. Though it has a different class of goods and/or services, it can  eliminate  the  uniqueness  of  the  famous  brand.  Second,  both  Indonesia  and  Thailand  have  not specifically regulated the brand dilution. Indonesia is only based on the overall protection on equality and/or equality in principle, while Thailand is only based protection on confusion.